PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH INVESTASI, UPAH MINIMUM REGIONAL DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA BARAT TAHUN 2002-2021 - Trihantana, Rully; Fariz, Muhamad Andi; Sundari, Deoh; Fitria, Meliana (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This study aims to determine the effect of Investment, Regional Minimum Wage and Changes in the Human Development Index on the Open Unemployment Rate in West Java Province in 2002-2021. This type of research is quantitative research using secondary data used in the form of time series data in the 2002-2021 observation period, which was obtained through the Badan Pusat Statistik. The analysis method used in this study is a multiple linear regression method processed using SPSS Version 26. The results showed that the independent variable has a significance value smaller than α (0.002<0.05) which means that the three independent variables together have a significant effect on the Open Unemployment Rate at an alpha value of 5% in West Java Province in 2002-2021. In the value of the coefficient of determination () the result of the Adjusted R Square value of 0.534 at a significance level of 5% mentioned that the dependent variable can be explained by the independent variable simultaneously by 53.4%, while the remaining 46.6% is explained by other factors or variables that were not mentioned in this study.